Viral safety of APOSECTM: a novel peripheral blood mononuclear cell derived-biological for regenerative medicine - Gugerell, Alfred (Blood Transfus, 2020)
BACKGROUND: Viral reduction and inactivation of cell-derived biologicals is paramount for patients’ safety and so viral reduction needs to be demonstrated to regulatory bodies in order to obtain marketing authorisation. Allogeneic human blood-derived biological medicinal products require special attention. APOSEC(TM), the secretome harvested from selected human blood cells, is a new biological with promising regenerative capabilities. We evaluated the effectiveness of inactivation of model viruses by methylene blue/light treatment, lyophilisation, and gamma irradiation during the manufacturing process of APOSEC(TM). MATERIALS AND METHODS: Samples of intermediates of APOSEC(TM) were acquired during the manufacturing process and spiked with bovine viral diarrhoea virus (BVDV), human immunodeficiency virus type 1 (HIV-1), pseudorabies virus (PRV), hepatitis A virus (HAV), and porcine parvovirus (PPV). Viral titres were assessed with suitable cell lines. RESULTS: Methylene blue-assisted viral reduction is mainly effective against enveloped viruses: the minimum log(10) reduction factors for BVDV, HIV-1, and PRV were ≥6.42, ≥6.88, and ≥6.18, respectively, with no observed residual infectivity. Viral titres of both HAV and PPV were not significantly reduced, indicating minor inactivation of non-enveloped viruses. Lyophilisation had minor effects on the viability of several enveloped model viruses. Gamma irradiation contributes to the viral safety by reduction of enveloped viruses (BVDV: ≥2.42; HIV-1: 4.53; PRV: ≥4.61) and to some degree of non-enveloped viruses as seen for HAV with a minimum log10 reduction factor of 2.92. No significant reduction could be measured for the non-enveloped virus PPV (2.60). DISCUSSION: Three manufacturing steps of APOSEC(TM) were evaluated under Good Laboratory Practice conditions for their efficacy at reducing and inactivating potentially present viruses. It could be demonstrated that all three steps contribute to the viral safety of APOSEC(TM).